Atividade curricular em habilidades sociais para professores de alunos do público alvo da Educação Especial - Lessa, Tatiane Cristina Rodrigues (2017)
With the increasing number of inclusion of students from the target audience of Special Education, there has been an increase in studies related to the topic as well. One of these topics refers to the need to focus on initial and continuing teacher training, which in addition to mastering curriculum knowledge needs to improve their interpersonal skills so that their educational action is more effective. Thus, this study aims to evaluate a curricular activity with experiences in social skills for undergraduate students and Special Education target audience students on their repertoire of social skills and educational social skills and to correlate social skills and abilities of the participants. A total of 19 teachers participated in this study, and the data collection took place in an activity called ACIEPE (Curricular Activities of Teaching, Research and Extension Integration) during 12 meetings, being the first and last meeting destined to apply the measurement instruments for pre and post evaluation – T-Test. As instruments, the Brazilian Criteria Questionnaire, the Social Skills Inventory (IHS-Del Prette), the Inventory of Educational Social Skills for Teachers (IHSE - Prof), the Social Skills Importance Scale, the Evaluation Questionnaire for Social Validation of the Program and Field journal. To the data analysis, the T-Test was performed for the comparison between pre and post-test data, as well as content analysis for the systematization of data from the questionnaires. The data showed that there were no differences in the social skills repertoire in the comparison between pre and post-test, but statistically significant differences were found to two factors related to social educational skills, and regarding to the greater importance attribution of the participants to the Classes of communicative and assertive social skills, advocacy and citizenship. In addition, we found a correlation between some specific items related to the social skills and educational social skills of the participants. In the evaluation of the characteristics of the course, the data pointed to the satisfaction of the participants regarding to the participation and format of the activities.